Hole transport material and preparation method thereof, solar cell, photovoltaic module and photovoltaic device

By using acidic group-modified trianyl structure organic compounds as hole transport materials in perovskite solar cells, the problem of insufficient wettability of the hole transport layer material is solved, and the photoelectric conversion efficiency and stability of the solar cell are improved.

CN119143797APending Publication Date: 2024-12-17CONTEMPORARY AMPEREX FUTURE ENERGY RES INST (SHANGHAI) LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202310715326.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The surface wetting of hole transport layer materials in existing perovskite solar cells is poor, resulting in the inability to form a continuous and uniform perovskite film, limiting the absorption of sunlight and cell efficiency.

Method used

Using organic compounds with specific structures as hole transport materials, the surface wetting and stability of the material is improved by introducing multiple acid groups on the trianiline structural unit. , and the material is prepared by polymerization or Ulman coupling reaction.

Benefits of technology

The surface wetting and stability of the hole transport layer is significantly improved, the photoelectric conversion efficiency of perovskite solar cells is enhanced, and the open circuit voltage, short circuit current and fill factor are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143797A_ABST
    Figure CN119143797A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cell materials, and provides a hole transport material and a preparation method thereof, a solar cell, a photovoltaic module and a photovoltaic device. The molecular structure general formula of the hole transport material is as shown in formula I. In the formula I, R1 comprises an acidic group; n is a natural number between 1 and 5; when n is 1, R2 is the same as R1, and when n is 2-5, R2 is hydrogen or is the same as R1. The hole transport material provided by the invention adopts an organic compound with a specific structure, the organic compound is a dendritic molecule formed by taking triphenylamine as a structural unit, and multiple active sites are modified on a pi conjugate surface of the molecule by adopting an acidic group, so that the wettability of the hole transport material can be increased, and the structural stability of the hole transport material can be improved; and a plurality of pi conjugate surfaces which are parallel to each other and parallel to the substrate can be formed, so that the stability of the solar cell is improved while good hole transmission capability is ensured, and the photoelectric conversion efficiency of the solar cell is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of solar cell materials, and in particular relates to a hole transport material and a preparation method thereof, a solar cell, a photovoltaic module and a photovoltaic device. Background Art

[0002] Perovskite materials are a type of semiconductor nanomaterials with uniform size and high color purity. Their elemental composition has a crystal structure similar to that of the mineral CaTiO3. Perovskite materials have strong light absorption capacity and a wide absorption range, and have great advantages in the field of optoelectronics. For example, perovskite solar cells (PSCs) with perovskite materials as the light-absorbing layer are developing rapidly.

[0003] A hole transport layer is generally set in a perovskite solar cell to increase its hole transport capacity. For example, a self-assembled monolayer (SAM) is used as the hole transport layer, but the current hole transport layer material has low wettability, which makes it impossible to form a continuous and uniform perovskite film on the surface of the hole transport layer, which restricts its absorption of sunlight to a certain extent. Summary of the invention

[0004] The purpose of the present application is to provide a hole transport material and a preparation method thereof, a solar cell, a photovoltaic module and a photovoltaic device, aiming to solve the problem of poor surface wettability of existing hole transport layer materials.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a hole transport material, and the molecular structure of the hole transport material is shown in Formula I:

[0007]

[0008] Wherein, R1 includes an acidic group; n is a natural number between 1 and 5; when n is 1, R2 is the same as R1, and when n=2 to 5, R2 is hydrogen or the same as R1.

[0009] In the technical solution of the embodiment of the present application, the hole transport material includes an organic compound with a specific structure, which is a dendritic molecule formed with triphenylamine as a structural unit. The N atoms contained in it can effectively improve the surface wettability of the hole transport material, and a continuous and uniform perovskite film can be obtained on its surface. In addition, the π conjugated surface of the molecule is modified with multiple active sites using acidic groups to form multiple π conjugated surfaces that are parallel to each other and to the substrate. While ensuring good hole transport ability, the stability of the hole transport material is effectively improved, thereby improving the photoelectric conversion efficiency of the solar cell.

[0010] In some embodiments, R1 includes any one of A-COOH, A-SO3H, A-PO3H2, and A-BO2H2; wherein A includes C0~C 10 Alkyl, C0~C 10 Any one of the alkoxy groups.

[0011] A plurality of hydrophilic acidic groups, such as A-COOH, A-SO3H, A-PO3H2 and A-BO2H2, are introduced at the position opposite to the N atom of the triphenylamine structural unit. The acidic groups can not only anchor the hole transport molecule in parallel to the substrate, but also effectively increase its hole transport capacity and fully improve its surface wettability, which is beneficial to form a continuous and uniform perovskite layer on its surface, thereby improving the photoelectric conversion efficiency of the solar cell.

[0012] In some embodiments, C0~C 10 The alkyl group includes any one of a C1-C4 straight chain alkyl group and a C5-C8 cycloalkyl group. 10 The alkoxy group includes any one of C1 to C4 straight chain alkoxy groups.

[0013] Introducing an acidic group connected by a linear alkyl group, an acidic group connected by a cycloalkyl group or an acidic group connected by an alkoxy group into the structural unit of triphenylamine so that the hole transport material is anchored in parallel on the substrate can effectively improve the hole transport ability of the hole transport material.

[0014] In some embodiments, the hole transport material includes at least one of the compounds shown in Formula Ia-Formula Id:

[0015]

[0016] In the technical solution of the embodiment of the present application, R2 is the same as R1, and R1 is selected from the group -C4H8PO3H2. The acidic group has a suitable electron-withdrawing ability, which can regulate the matching degree between the energy level of the hole transport material and the energy level of the perovskite light-absorbing layer, thereby effectively improving its hole transport ability.

[0017] In some embodiments, the hole transport material includes a compound represented by Formula Ia and a compound represented by Formula Ib, and the mass ratio of the compound represented by Formula Ia to the compound represented by Formula Ib is (2-3):(0.5-1.5). The compound represented by Formula Ia (t4PATAA) and the compound represented by Formula Ib (t4PADTAA) have similar numbers of acidic groups and similar energy levels, which is more conducive to matching the energy level of the perovskite transport layer.

[0018] In a second aspect, the present application provides a method for preparing a hole transport material, comprising the following steps:

[0019] Step S10, using the compound represented by Formula II and the compound represented by Formula III as monomers, performing a polymerization reaction to obtain the hole transport material of the present application;

[0020]

[0021] or,

[0022] Step A10, using the compound represented by Formula IV and the compound represented by Formula V as monomers, performing an Ullmann coupling reaction to obtain the hole transport material of the present application;

[0023]

[0024] Wherein, X includes any one of the halogen elements.

[0025] In the technical solution provided in the embodiment of the present application, a triphenylamine containing R2 and / or R1 substituents is used as a monomer to carry out a polymerization reaction to obtain a dendritic molecule. In addition, the preparation method of the hole transport material provided by the present invention is simple to operate, reliable and controllable, has low production cost, high yield, and is conducive to large-scale production and application.

[0026] In some embodiments, R1 includes any one of A-COOH, A-SO3H, A-PO3H2, and A-BO2H2, and A includes C0~C 10 Alkyl, C0~C 10 Any one of the alkoxy groups.

[0027] By introducing acidic groups such as A-COOH, A-SO3H, A-PO3H2, and A-BO2H2 at the position opposite to the N atom of the triphenylamine structural unit, a hole transport material having multiple acidic groups can be obtained.

[0028] In some embodiments, C0~C 10 The alkyl group includes any one of a C1-C4 straight chain alkyl group and a C5-C8 cycloalkyl group. 10 The alkoxy group includes any one of C1 to C4 straight chain alkoxy groups.

[0029] Introducing an acidic group connected by a linear alkyl group, an acidic group connected by a cycloalkyl group or an acidic group connected by an alkoxy group into the structural unit of triphenylamine can effectively improve the hole transport capacity of the material.

[0030] In some embodiments, X comprises any one of bromine, chlorine, and iodine.

[0031] X is a halogen element, so that the monomer undergoes polymerization reaction at the position where the X atom is located to obtain the hole transport material shown in formula I.

[0032] In some embodiments, the polymerization step includes: subjecting the compound of formula II to a substitution reaction so that the X atom in the compound of formula II is replaced by a borate group, and then subjecting the compound of formula II or the compound of formula III to a Suzuki coupling reaction.

[0033] In some embodiments, the polymerization step includes: subjecting the compound of formula III to a substitution reaction, so that the X atom in the compound of formula III is replaced by a borate group, and then subjecting the compound of formula II or the compound of formula III to a Suzuki coupling reaction.

[0034] In some embodiments, the Suzuki coupling reaction is carried out under a first catalyst comprising tetrakis(triphenylphosphine)palladium and potassium carbonate.

[0035] In some embodiments, the reaction temperature of the Suzuki coupling reaction is 70-90°C.

[0036] In some embodiments, the Ullmann coupling reaction is carried out under the conditions of a second catalyst, and the second catalyst includes cuprous iodide, sodium tert-butoxide and 1-10,1-phenanthroline.

[0037] In a third aspect, the present application provides a solar cell, comprising a hole transport layer, wherein the hole transport layer comprises the hole transport material of the present application and / or the hole transport material prepared by the preparation method of the hole transport material of the present application.

[0038] In the technical solution of the embodiment of the present application, by using an organic compound with a specific structure in the hole transport layer, its surface wettability can be effectively improved. The hole transport layer contains multiple π-conjugated planes that are parallel to each other and parallel to the substrate, which can reduce the energy level barrier between the light absorbing layer and the lower interface, thereby reducing the loss of hole transport, thereby significantly improving the open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the solar cell.

[0039] In some embodiments, a solar cell includes a first electrode layer, a perovskite light absorbing layer, a hole transport layer, and a second electrode layer.

[0040] In some embodiments, the thickness of the hole transport layer is

[0041] In some embodiments, the hole mobility of the hole transport layer is 1.73×10 -4 ~3.58×10 -3 cm 2 ·V -1 ·s -1 .

[0042] In some embodiments, the band gap of the perovskite light absorbing layer is 1.10-2.0 eV.

[0043] In some embodiments, the thickness of the perovskite light absorbing layer is between 600 nm and 800 nm.

[0044] In a fourth aspect, the present application provides a photovoltaic assembly comprising the solar cell of the present application.

[0045] In the technical solution of the embodiment of the present application, since the solar cell of the present application is included, the solar cell has a higher photoelectric conversion efficiency, thus ensuring that the photovoltaic module has a higher photoelectric conversion efficiency.

[0046] In a fifth aspect, the present application provides a photovoltaic device, comprising the photovoltaic module of the present application.

[0047] In the technical solution of the embodiment of the present application, since the photovoltaic component of the present application is included, the photovoltaic component has a higher photoelectric conversion efficiency, thus ensuring that the photovoltaic device has a higher photoelectric conversion efficiency.

[0048] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0050] Figure 1 is a schematic diagram of the structure of a solar cell provided in an embodiment of the present application;

[0051] Among them, the reference numerals in the specific implementation manner are as follows:

[0052] A first electrode layer 110 , a hole transport layer 120 , a perovskite light absorbing layer 130 , an electron transport layer 140 , and a second electrode layer 150 . DETAILED DESCRIPTION

[0053] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0055] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0057] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0058] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0059] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0060] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0061] In the present application, the term "SAM" is an abbreviation of "self-assembled monolayer", which means self-assembled monolayer.

[0062] In the present application, the term "acidic group" refers to a group that can generate hydrogen ions when hydrolyzed or ionized, for example, -COOH, -SO3H, -PO3H2, etc. Hydrogen atoms connected to a benzene ring are generally difficult to form hydrogen protons under hydrolysis or ionization conditions. Based on this, hydrogen atoms are not included in the acidic groups of the present application.

[0063] In the present application, the term "Suzuki coupling reaction" means Suzuki coupling reaction.

[0064] In the present application, the term "Ullmann coupling reaction" means an Ullmann coupling reaction.

[0065] Compared with the upright nip-type perovskite solar cells, the inverted pin-type perovskite solar cells have the advantages of small hysteresis effect, no need for carrier doping, good stability, etc., and are regarded as commercializable perovskite solar cells. In the inverted structure perovskite solar cells, the perovskite light absorption layer is deposited on the hole transport layer. Therefore, the film quality of the hole transport layer determines the quality of the perovskite light absorption layer, which in turn affects the photoelectric conversion efficiency and service life of the battery device.

[0066] Inverted perovskite solar cells often use self-assembled monolayer materials (SAM) as hole transport layers. SAMs molecules are mainly composed of head connecting groups, main chains and end groups. They have attracted widespread attention due to their advantages such as low parasitic absorption, high material utilization, adjustable substrate energy levels, and functional groups that can passivate the active layer. At present, SAMs molecules have both hydrophobic and hydrophilic molecular structures. However, the surface wettability of SAMs molecules is not ideal, and it is difficult to form a continuous and uniform perovskite light-absorbing layer on its surface, which restricts its absorption of solar energy to a certain extent. Even if part of the hole transport layer is exposed on the surface, the perovskite light-absorbing layer is not successfully coated on its surface, and an effective perovskite cell cannot be formed.

[0067] The end groups in SAMs molecules are active groups that determine the overall performance of the self-assembled monolayer surface and are the key factors affecting the surface wettability of SAMs. However, there is currently no accurate reaction mechanism for how different end groups affect the surface wettability, which increases the difficulty of improving the surface wettability of SAMs molecules.

[0068] Based on the above considerations, in order to improve the surface wettability of the hole transport layer, a hole transport material is designed, which is a dendritic molecule formed with triphenylamine as a structural unit, and an acidic group is connected to the position of the nitrogen atom of triphenylamine. Its structural formula is shown in Formula I:

[0069]

[0070] Wherein, R1 includes an acidic group; n is a natural number between 1 and 5; when n is 1, R2 is the same as R1, and when n=2 to 5, R2 is hydrogen or the same as R1.

[0071] The hole transport material includes a self-assembled monolayer (SAM) formed with triphenylamine as a structural unit. The π conjugated surface of the SAM molecule is modified with multiple active sites using acidic groups, which can not only increase the wettability of the SAM molecule and improve its structural stability, but also form multiple π conjugated surfaces that are parallel to each other and to the substrate. In this way, while ensuring good hole transport capability, the stability of the solar cell is improved, thereby improving the photoelectric conversion efficiency of the solar cell.

[0072] In addition, in the above hole transport material, the degree of polymerization of the structural unit triphenylamine is a natural number between 1 and 5. If the amount of triphenylamine contained in the hole transport material is too high, the SAM molecules will spontaneously stack vertically on the substrate, and the π conjugated plane formed may be perpendicular to the substrate or form a certain angle with the substrate, thereby seriously affecting the hole transport ability.

[0073] In some of the examples, R1 includes any one of A-COOH, A-SO3H, A-PO3H2, and A-BO2H2; wherein A includes C0~C 10 Alkyl, C0~C 10 Any one of the alkoxy groups.

[0074] A plurality of hydrophilic acidic groups, such as A-COOH, A-SO3H, A-PO3H2 and A-BO2H2, are introduced at the position opposite to the N atom of the triphenylamine structural unit. The acidic groups have appropriate electron-withdrawing ability and can adjust the energy level of the hole transport material so that the energy level of the hole transport layer matches the energy level of the perovskite light-absorbing layer. The acidic groups can also serve as anchoring groups to completely cover and bond the hole transport material on the surface of the substrate and form a plurality of π-conjugated planes parallel to each other and to the substrate, thereby effectively improving the surface wettability, which is beneficial to forming a continuous and uniform perovskite layer on the surface, and at the same time fully increasing the hole transport capacity, further improving the photoelectric conversion efficiency of the solar cell.

[0075] In some of these examples, C0~C 10 The alkyl group includes any one of a C1-C4 straight chain alkyl group and a C5-C8 cycloalkyl group. 10 The alkoxy group includes any one of C1 to C4 straight chain alkoxy groups.

[0076] Introducing an acidic group connected by a linear alkyl group, an acidic group connected by a cycloalkyl group or an acidic group connected by an alkoxy group into the structural unit of triphenylamine so that the hole transport material is anchored in parallel on the substrate can effectively improve the hole transport ability of the hole transport material.

[0077] For example, A-COOH includes -COOH, -CH2COOH, -C2H4COOH, -C3H6COOH, -C4H8COOH, Any one of -OCH2COOH, -OC2H4COOH, and -OC3H6COOH.

[0078] For example, A-SO3H includes -SO3H, -CH2SO3H, -C2H4SO3H, -C3H6SO3H, -C4H8SO3H, Any one of -OCH2SO3H, -OC2H4SO3H, -OC3H6SO3H.

[0079] Exemplarily, A-PO3H2 includes -PO3H2, -CH2PO3H2, -C2H4PO3H2, -C3H6PO3H2, -C4H8PO3H2, Any one of -OCH2PO3H2, -OC2H4PO3H2, -OC3H6PO3H2.

[0080] For example, A-BO2H2 includes -BO2H2, -CH2-BO2H2, -C2H4-BO2H2, -C3H6-BO2H2, -C4H8-BO2H2, Any one of -OCH2BO2H2, -OC2H4BO2H2, -OC3H6BO2H2.

[0081] In some examples, the hole transport material includes at least one of the compounds shown in Formula Ia-Formula Id:

[0082]

[0083] In the hole transport material provided in the embodiment of the present application, R2 is the same as R1, and R1 is selected from the group -C4H8PO3H2. The acidic group has a suitable electron-withdrawing ability, which can regulate the matching degree between the energy level of the hole transport material and the energy level of the perovskite light-absorbing layer, thereby effectively improving its hole transport ability. It can also enable the SAM molecules to be anchored in parallel on the substrate, so that the SAM molecules include a number of π-conjugated planes that are parallel to each other and parallel to the substrate. In this way, while improving the hole transport ability, its structural stability is effectively improved, thereby increasing the open circuit voltage of the solar cell.

[0084] In some of the examples, the hole transport material includes a compound shown in Formula Ia and a compound shown in Formula Ib. The compound shown in Formula Ia (t4PATAA) and the compound shown in Formula Ib (t4PADTAA) have similar cohesive forces, so that the two SAM molecules have the same orientation, so that the surface wettability of both can be fully utilized, thereby effectively improving the hole transport capacity of the hole transport material. At the same time, the two also have a similar number of acidic groups and their energy levels are close, which is more conducive to matching the energy level of the perovskite transport layer.

[0085] In some of the examples, the mass ratio of the compound represented by Formula Ia to the compound represented by Formula Ib is 2 to 3:0.5 to 1.5. Within the range of the mass ratio of the compound represented by Formula Ia to the compound represented by Formula Ib provided in the application embodiment, the energy level barrier between the perovskite light absorption layer and the lower interface can be reduced, effectively reducing the loss of hole transmission, thereby effectively improving the open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the perovskite solar cell.

[0086] In some of these examples, the mass ratio of the compound represented by Formula Ia to the compound represented by Formula Ib includes but is not limited to 3:1, 2:0.5, 2.5:1, 2:1, 3:0.5, and 2:1.5.

[0087] A second aspect of the present application provides a method for preparing a hole transport material, comprising the following steps:

[0088] Step S10, using the compound represented by Formula II and the compound represented by Formula III as monomers, performing a polymerization reaction to obtain the hole transport material of the present application;

[0089]

[0090]

[0091] Wherein, X includes any one of the halogen elements.

[0092] The preparation method of the hole transport material provided in the embodiment of the present application is to perform a coupling reaction with triphenylamine containing R2 and / or R1 substituents to obtain a dendritic molecule, which forms a plurality of π-conjugated planes parallel to each other and to the substrate, so that the hole transport material has a high hole transport capacity. In addition, the preparation method of the hole transport material provided by the present invention is simple to operate, reliable and controllable, has low production cost, high yield, and is conducive to large-scale production and application.

[0093] In some examples, in the compound represented by formula II and the compound represented by formula III: R1 includes an acidic group, R2 is hydrogen or the same as R1. Wherein R1 includes any one of A-COOH, A-SO3H, A-PO3H2, A-BO2H2, A includes C0~C 10 Alkyl, C0~C 10 Any one of the alkoxy groups.

[0094] By introducing acidic groups such as A-COOH, A-SO3H, A-PO3H2, and A-BO2H2 at the position opposite to the N atom of the triphenylamine structural unit, a hole transport material having multiple acidic groups can be obtained.

[0095] In some of these examples, C0~C 10 The alkyl group includes any one of a C1-C4 straight chain alkyl group and a C5-C8 cycloalkyl group. 10 The alkoxy group includes any one of C1 to C4 straight chain alkoxy groups.

[0096] Introducing an acidic group connected by a linear alkyl group, an acidic group connected by a cycloalkyl group or an acidic group connected by an alkoxy group into the structural unit of triphenylamine can effectively improve the hole transport capacity of the material.

[0097] In some examples, X includes any one of bromine, chlorine, and iodine. X is a halogen element, so that the monomer undergoes polymerization reaction at the position where the X atom is located to obtain the hole transport material shown in Formula I.

[0098] In some of the examples, the polymerization reaction steps include: subjecting the compound of formula II to a substitution reaction so that the X atom in the compound of formula II is replaced by a borate group, and then subjecting the compound of formula II or the compound of formula III to a Suzuki coupling reaction.

[0099] In some specific examples, the steps of the polymerization reaction include:

[0100] The compound represented by formula II is used as a monomer, and then the monomer is subjected to a substitution reaction, so that the X atom in the compound represented by formula II is replaced by a borate group, thereby obtaining an intermediate containing a borate;

[0101] The intermediate containing the borate ester is subjected to a Suzuki coupling reaction with the compound shown in Formula II or the compound shown in Formula III to obtain the hole transport material shown in Formula I.

[0102] Exemplarily, the compound represented by formula II is used as a monomer, the monomer is subjected to a substitution reaction with a boric ester, and then subjected to a Suzuki coupling reaction with the monomer to obtain a hole transport material represented by formula I. The specific synthesis route is as follows:

[0103]

[0104] In some of the examples, the polymerization reaction step includes: subjecting the compound of formula III to a substitution reaction so that the X atom in the compound of formula III is replaced by a borate group, and then subjecting the compound of formula II or the compound of formula III to a Suzuki coupling reaction.

[0105] In some specific examples, the steps of the polymerization reaction include:

[0106] The compound represented by formula III is used as a monomer, and then the monomer is subjected to a substitution reaction, so that the X atom in the compound represented by formula III is replaced by a borate group, thereby obtaining an intermediate containing a borate;

[0107] The intermediate containing the borate ester is subjected to a Suzuki coupling reaction with the compound shown in Formula II or the compound shown in Formula III to obtain the hole transport material shown in Formula I.

[0108] Exemplarily, the compound represented by formula III is used as a monomer, the monomer is subjected to a substitution reaction with a boric ester, and then subjected to a Suzuki coupling reaction with a compound represented by formula II to obtain a hole transport material represented by formula I. The specific synthesis route is as follows:

[0109]

[0110] Exemplarily, the compound represented by formula II is used as a monomer, the monomer is subjected to a substitution reaction with a boric ester, and then subjected to a Suzuki coupling reaction with the compound represented by formula III to obtain an intermediate material; the intermediate material is used as a monomer, the monomer is subjected to a substitution reaction with a boric ester, and then subjected to a Suzuki coupling reaction with the intermediate material to obtain a hole transport material represented by formula I. The specific synthesis route is as follows:

[0111]

[0112]

[0113] Based on the difference in the degree of polymerization of hole transport materials, the present embodiment provides a method for preparing a hole transport material, comprising the following steps:

[0114] Step A10, using the compound represented by Formula IV and the compound represented by Formula V as monomers, performing an Ullmann coupling reaction to obtain the hole transport material of the present application;

[0115]

[0116] Wherein, X includes any one of the halogen elements.

[0117] Exemplarily, the specific synthesis route of step A10 is as follows:

[0118]

[0119] In some specific examples, the preparation method of the compound represented by Formula II comprises the following steps:

[0120] 4-R2-halobenzene and 4-halogen-aniline are subjected to Ullmann coupling reaction to obtain a compound shown in Formula II. In the preparation process of the compound shown in Formula II, the amount of 4-R2-halobenzene added can be excessive relative to 4-halogen-aniline, so that each raw material component can be fully reacted to obtain a compound shown in Formula II with high purity and high yield. Specifically, the molar ratio of 4-R2-halobenzene to 4-halogen-aniline includes but is not limited to 2:1, 2.05:1, 2.1:1, and 2.2:1.

[0121] The specific synthetic route of the above reaction is as follows:

[0122]

[0123] In some specific examples, the preparation method of the compound represented by Formula III comprises the following steps:

[0124] 4-halogen-iodobenzene and 4-R1-aniline are subjected to Ullmann coupling reaction to obtain the compound shown in formula III. In the preparation process of the compound shown in formula III, the addition amount of 4-halogen-iodobenzene is excessive relative to 4-R1-aniline, so that each raw material component can be fully reacted to obtain a compound shown in formula III with high purity and high yield. Specifically, the molar ratio of 4-R1-aniline to 4-halogen-iodobenzene includes but is not limited to 1:2, 1:2.05, 1:2.1, and 1:2.2.

[0125] The specific synthetic route of the above reaction is as follows:

[0126]

[0127] In some of these examples, the suzuki coupling reaction is carried out in the presence of a first catalyst comprising tetrakis(triphenylphosphine)palladium and potassium carbonate.

[0128] In some specific examples, the mass ratio of tetrakis(triphenylphosphine)palladium to potassium carbonate is 5-7:135-140.

[0129] In some specific examples, the first catalyst accounts for 30-40 wt % of the total mass of the reaction raw materials.

[0130] In some of these examples, the reaction temperature of the Suzuki coupling reaction is 70-90°C.

[0131] In some specific examples, the temperature of the Suzuki coupling reaction can be 70° C., 75° C., 80° C., 85° C., 90° C. or within a range consisting of any of the above values.

[0132] In some specific examples, the reaction solvent for the Suzuki coupling reaction includes tetrahydrofuran.

[0133] In some of these examples, the Ullmann coupling reaction is carried out in the presence of a second catalyst comprising cuprous iodide, sodium tert-butoxide and 1-10,1-phenanthroline.

[0134] In some examples, the amount of the second catalyst added is 30-40 wt % of the total mass of the reaction raw materials.

[0135] In some of the examples, the mass ratio of cuprous iodide, sodium tert-butoxide and 1-10,1-phenanthroline is 0.8-1.2:0.8-1.2:0.1-0.3.

[0136] In some of these examples, the reaction solvent for the Ullmann coupling reaction includes toluene.

[0137] A third aspect of an embodiment of the present application provides a solar cell, comprising a hole transport layer, wherein the hole transport layer comprises the hole transport material of the present application or a hole transport material prepared according to the preparation method of the hole transport material of the present application.

[0138] The solar cell provided in the third aspect of the embodiment of the present application adopts an organic compound with a specific structure in the hole transport layer, which includes multiple π-conjugated planes parallel to each other and parallel to the substrate. This can reduce the energy level barrier between the light absorbing layer and the lower interface, thereby reducing the loss of hole transport, thereby significantly improving the open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the solar cell.

[0139] In some of these examples, the thickness of the hole transport layer is Within the thickness range of the hole transport layer provided in the embodiments of the present application, while ensuring that the hole transport layer has a high hole transport capacity, electron loss can also be avoided, further improving the efficiency of the solar cell. Specifically, the thickness of the hole transport layer includes but is not limited to

[0140] In some of these examples, the hole mobility of the hole transport layer is 1.73×10 -4 ~3.58×10 -3 cm 2 ·V -1 ·s -1 Specifically, the hole mobility of the hole transport layer can be 1.73×10 -4 cm 2 ·V -1 ·s -1 , 2.5×10 -4 cm 2 ·V -1 ·s -1 , 5×10 -4 cm 2 ·V -1 ·s -1 , 7.5×10 -4 cm 2 ·V -1 ·s -1 , 1.5×10 -3 cm 2 ·V -1 ·s -1 , 1.91×10 - 3 cm 2 ·V -1 ·s -1 ,3.58×10 -3 cm 2 ·V -1·s -1 Or within the range consisting of any of the above values.

[0141] In some examples, the method of preparing the hole transport layer includes:

[0142] Step B1, dissolving a hole transport material in an organic solvent to prepare a hole transport solution;

[0143] Step B2: subjecting the hole transport solution to film-forming treatment.

[0144] In some examples, the organic solvent includes one or more of isopropyl alcohol, toluene, chlorobenzene, and anisole.

[0145] In some examples, the concentration of the hole transport solution is 0.5-5 mg / mL. Specifically, the concentration of the hole transport layer solution includes but is not limited to 0.5 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL, and 5 mg / mL.

[0146] In some of the examples, the film forming treatment method can be a method well known in the art. Specifically, the film forming treatment method includes but is not limited to a sol-gel method, a blade coating method, and a slit coating method. The organic solvent can then be removed by annealing or vacuum.

[0147] In some of these examples, a solar cell includes a first electrode layer, a perovskite layer, a hole transport layer, and a second electrode layer.

[0148] In some of these examples, the solar cell may include both a formal and a trans form.

[0149] In some specific examples, a formal solar cell includes a first electrode layer, and an electron transport layer, a perovskite light absorption layer, a hole transport layer, and a second electrode layer stacked in sequence on the first electrode layer.

[0150] In some specific examples, the inverted solar cell includes a first electrode layer and a hole transport layer, a perovskite light absorption layer, an electron transport layer, and a second electrode layer sequentially stacked on the first electrode layer.

[0151] In some specific examples, the solar cell is formal, and the preparation method thereof includes the following steps:

[0152] Step S1: etching and cleaning the transparent first electrode, and drying;

[0153] Step S2: preparing an electron transport layer on the first electrode layer;

[0154] Step S3: preparing a perovskite light absorbing layer on the electron transport layer;

[0155] Step S4: preparing a hole transport layer on the perovskite light absorbing layer;

[0156] Step S5: preparing a second electrode layer on the hole transport layer.

[0157] In some specific examples, the solar cell is transverse, and the preparation method thereof includes the following steps:

[0158] Step S1: etching and cleaning the first electrode, and drying;

[0159] Step S2: preparing a hole transport layer on the first electrode layer;

[0160] Step S3: preparing a perovskite light absorbing layer on the hole transport layer;

[0161] Step S4: preparing an electron transport layer on the perovskite light absorbing layer;

[0162] Step S5: preparing a second electrode layer on the electron transport layer.

[0163] In some specific examples, the first electrode includes a transparent conductive glass substrate. Specifically, the material of the transparent conductive glass substrate includes but is not limited to FTO, ITO, AZO, BZO or IZO glass.

[0164] In some specific examples, the second electrode layer may be an organic conductive material, an inorganic conductive material, or a hybrid conductive material of an organic and inorganic material. Specifically, the material of the second electrode layer includes but is not limited to at least one of Ag, Cu, C, Au, Al, ITO, AZO, BZO, IZO, and IWO.

[0165] In some specific examples, the material of the electron transport layer may be a commonly used electron transport material in the art. Specifically, the electron transport material includes but is not limited to [6,6]-phenyl C61 butyric acid methyl ester (PC61BM), [6,6]-phenyl C71 butyric acid methyl ester (PC71BM), fullerene C60 (C60), fullerene C70 (C70), tin dioxide (SnO2) or zinc oxide (ZnO).

[0166] In some specific examples, the perovskite light-absorbing layer includes a light-absorbing material with a chemical formula of ABX3, wherein A and B independently include at least one of an inorganic cation and an organic cation, and X includes at least one of an inorganic anion and an organic anion.

[0167] In some specific examples, A includes CH3NH3 + 、HC(NH2)2 + 、CH2(NH3)2 + At least one of; and / or, B includes Pb2+ Sn 2+ At least one of; and / or, X comprises Br - ,I - , Cl - At least one of .

[0168] In some examples, the band gap of the perovskite light absorbing layer is 1.10 to 2.0 eV. The band gap of the perovskite light absorbing layer can be measured using a commonly used test method in the art, such as using the XPS related data processing function in the Avantage software.

[0169] In some examples, the thickness of the perovskite light absorbing layer is between 600 and 800 nm. Specifically, the thickness of the perovskite light absorbing layer can be 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, or any range thereof.

[0170] A fourth aspect of an embodiment of the present application provides a photovoltaic assembly, including the solar cell of the present application.

[0171] Since the photovoltaic module includes the solar cell of the present application, the solar cell has a high photoelectric conversion efficiency, thus ensuring that the photovoltaic module has a high photoelectric conversion efficiency.

[0172] In some examples, the photovoltaic module includes one or more solar cells, which can be selected according to specific application scenarios. Specifically, the photovoltaic module includes multiple solar cells, and the multiple solar cells are connected in series or in parallel to form a battery cell.

[0173] In some examples, the photovoltaic module further includes a photovoltaic glass layer, a bonding layer, and a back sheet.

[0174] In some specific examples, adhesive layers are provided on both surfaces of the cell, a back sheet is provided on the surface away from the cell in one of the adhesive layers, and a photovoltaic glass layer is provided on the surface away from the cell in the other adhesive layer. The photovoltaic glass layer and the back sheet are used to protect the solar cells, seal, insulate, and waterproof; the adhesive layer serves to bond the photovoltaic glass layer to the cell, and to bond the back sheet to the cell.

[0175] In some specific examples, the photovoltaic module also includes a junction box and an outer frame. The junction box is used to protect the power generation system of the entire photovoltaic module. It is equivalent to a current transfer station. When a battery cell short-circuits, the junction box will automatically disconnect the short-circuited battery string. The outer frame can support and protect the entire photovoltaic module. The frame can be made of aluminum alloy, which has excellent strength and corrosion resistance.

[0176] A fifth aspect of an embodiment of the present application provides a photovoltaic device, including the photovoltaic component of the present application.

[0177] The photovoltaic device utilizes the photovoltaic effect of the solar cells in the photovoltaic module it includes to convert solar energy into electrical energy and has a high photoelectric conversion efficiency. In this way, it can be ensured that the photovoltaic device has a high photoelectric conversion efficiency.

[0178] In some examples, the photovoltaic device is a photovoltaic power generation device. The photovoltaic module is the core part of the photovoltaic power generation device. The photovoltaic device includes one or more photovoltaic modules, which can be selected according to the specific application scenario. Specifically, when the photovoltaic device includes multiple photovoltaic modules, the multiple photovoltaic modules form a photovoltaic array.

[0179] In some examples, the photovoltaic device may be an independent photovoltaic power generation device or a grid-connected photovoltaic power generation device. An appropriate photovoltaic device may be selected according to the application scenario.

[0180] The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0181] Example A1

[0182] This embodiment provides a hole transport material and a preparation method thereof.

[0183] A hole transport material, denoted as material A1, has the following structural formula:

[0184]

[0185] A method for preparing a hole transport material comprises the following steps:

[0186]

[0187] Step 1: 6.02 g (17.7 mmol) of iodobenzene p-butylphosphonate, 1.94 g (8.85 mmol) of aniline p-butylphosphonate, and 200 mg (1.10 mmol) of 1,10-phenanthroline were placed in a 250 mL three-necked flask containing 100 mL of toluene. After dissolving, 1 g of cuprous iodide and 1 g of sodium tert-butoxide were added. After reacting at room temperature for 12 hours, 20 mL of water was added to quench the reaction. The toluene solution was extracted twice with water, and toluene was extracted once with saturated brine, and the organic phase was collected. After the organic phase was rotary evaporated at 75°C to remove toluene, 3.7 g of crude product (yield: 77.3%) was obtained, and its chemical formula is shown in Formula Ia.

[0188] NMR test of material A1 (CDCl3, 400MHz, δ):

[0189] 1 H NMR:7.18(d,J=7.5Hz,6H),7.03(d,J=7.5Hz,6H),4.87(s,6H),2.55(t,J=7.1 Hz, 6H), 1.73 (t, J = 11.9 Hz, 6H), 1.52 (m, J = 7.1 Hz, 6H), 1.25 (m, J = 7.1 Hz, 6H).

[0190] Example A2

[0191] This embodiment provides a hole transport material and a preparation method thereof.

[0192] A hole transport material, denoted as material A2, has the following structural formula:

[0193]

[0194] A method for preparing a hole transport material comprises the following steps:

[0195]

[0196] Step 1: 5.0 g (14.7 mmol) of iodobenzene p-butylphosphonate, 1.26 g (7.35 mmol) of 4-bromoaniline, and 200 mg (1.10 mmol) of 1,10-phenanthroline were placed in a 250 mL three-necked flask containing 100 mL of toluene. After dissolving, 1 g of cuprous iodide and 1 g of sodium tert-butoxide were added. After reacting at room temperature for 12 hours, 20 mL of water was added to quench the reaction. The toluene solution was extracted twice with water, and toluene was extracted once with saturated brine, and the organic phase was collected. After the organic phase was rotary evaporated at 75°C to remove toluene, 3.0 g of crude product (yield: 78.3%) was obtained, which was recorded as IIa.

[0197] Step 2: 2 g of crude product IIa was put into a 250 mL three-necked flask containing 100 mL of tetrahydrofuran, and after dissolving, 1 mL of n-butyl lithium and 0.52 g (5 mmol) of trimethyl borate were added at -78°C, and reacted at room temperature for 3 h. Then, 70 mg (0.6 mmol) of Pd(PPh3)4, 1.38 g (10 mmol) of K2CO3, and 2 g of crude product IIa were added to the three-necked flask, and the temperature was raised to 80°C and reacted for 48 h. After reacting for 48 h, the solvent was dried, 50 mL of anhydrous ethanol was added, the insoluble matter was filtered off, and 50 mL of ether was added for recrystallization to obtain 3.0 g of white crystals of the product (yield: 88.7%), and its chemical formula is shown in Formula Ib.

[0198] NMR test of material A2 (CDCl3, 400MHz, δ):

[0199] 1H NMR: 7.75(d,J=6.8Hz,8H),7.57(d,J=5.2Hz,8H),7.43(d,J=6.3Hz,4H),7.10(d,J=6.4Hz ,4H),4.80(s,8H),2.52(t,J=4.2Hz,8H),1.66(t,J=4.4Hz,8H),1.59(m,8H),1.26(m,8H).

[0200] Example A3

[0201] This embodiment provides a hole transport material and a preparation method thereof.

[0202] A hole transport material, denoted as material A3, has the following structural formula:

[0203]

[0204] A method for preparing a hole transport material comprises the following steps:

[0205]

[0206]

[0207] Step 1: 5.0 g (17.7 mmol) of p-bromoiodobenzene, 1.94 g (8.85 mmol) of p-butylphosphonic acid aniline, and 200 mg (1.10 mmol) of 1,10-phenanthroline were placed in a 250 mL three-necked flask containing 100 mL of toluene. After dissolving, 1 g of cuprous iodide and 1 g of sodium tert-butoxide were added. After reacting at room temperature for 12 hours, 20 mL of water was added to quench the reaction. The toluene solution was extracted twice with water, and toluene was extracted once with saturated brine, and the organic phase was collected. After the organic phase was rotary evaporated at 75°C to remove toluene, 3.7 g of crude product (yield: 77.3%) was obtained, which was recorded as IIIa.

[0208] Step 2: 2 g of crude product IIIa was put into a 250 mL three-necked flask containing 100 mL of tetrahydrofuran, and after dissolving, 2 mL of n-butyl lithium and 1.04 g (10 mmol) of trimethyl borate were added at -78°C, and reacted at room temperature for 3 h. Then, 140 mg (1.2 mmol) of Pd(PPh3)4, 2.76 g (20 mmol) of K2CO3, and 3.83 g of crude product IIa were added to the three-necked flask, and the temperature was raised to 80°C and reacted for 48 h. After reacting for 48 h, the solvent was dried, 50 mL of anhydrous ethanol was added, the insoluble matter was filtered off, and 50 mL of ether was added for recrystallization to obtain 4.5 g of white crystals of the product (yield: 91.0%), the chemical formula of which is shown in Formula Ic.

[0209] NMR test of material A3 (CDCl3, 400MHz, δ):

[0210] 1 H NMR:12.7(s,10H),7.55(m,8H),7.25(m,8H),7.05(m,20H),2.55(t,J=7.3Hz, 10H), 1.68 (t, J=7.0Hz, 10H), 1.54 (t, J=7.8Hz, 10H), 1.21 (t, J=7.1Hz, 10H).

[0211] Example A4

[0212] This embodiment provides a hole transport material and a preparation method thereof.

[0213] A hole transport material, denoted as material A4, has the following structural formula:

[0214]

[0215] A method for preparing a hole transport material comprises the following steps:

[0216]

[0217]

[0218] Step 1: 2 g of crude product IIa was put into a 250 mL three-necked flask containing 100 mL of tetrahydrofuran, and after dissolution, 1 mL of n-butyl lithium and 5.02 g (5 mmol) of trimethyl borate were added at -78°C, and reacted at room temperature for 3 h. Then, 70 mg (0.6 mmol) of Pd(PPh3)4, 1.38 g (10 mmol) of K2CO3, and 4.18 g of crude product IIIa were added to the three-necked flask, and the temperature was raised to 80°C and reacted for 48 h. After reacting for 48 h, the solvent was dried, 50 mL of anhydrous ethanol was added, the insoluble matter was filtered off, and 50 mL of ether was added for recrystallization to obtain 3.1 g of white crystals of the product (yield: 82.3%), which was recorded as A4-1.

[0219] Step 2: 2 g of crude product A4-1 was put into a 250 mL three-necked flask containing 100 mL of tetrahydrofuran, and after dissolution, 1 mL of n-butyl lithium and 0.52 g (5 mmol) of trimethyl borate were added at -78°C, and reacted at room temperature for 3 h. Then, 70 mg (0.6 mmol) of Pd(PPh3)4, 1.38 g (10 mmol) of K2CO3, and 2 g of crude product A4-1 were added to the three-necked flask, and the temperature was raised to 80°C and reacted for 48 h. After reacting for 48 h, the solvent was dried, 50 mL of anhydrous ethanol was added, the insoluble matter was filtered off, and 50 mL of ether was added for recrystallization to obtain 3.0 g of white crystals of the product (yield: 81.7%), the structural formula of which is shown in Formula Id.

[0220] NMR test of material A4 (CDCl3, 400MHz, δ):

[0221] 1 H NMR: 3.7(s,10H),7.67(m,12H),7.21(m,12H),7.10(m,24H),2.51(t,J=7.3Hz ,12H), 1.61(t,J=7.0Hz,12H), 1.54(t,J=7.8Hz,12H), 1.29(t,J=7.1Hz,12H).

[0222] Example B1

[0223] A perovskite solar cell having a structure such as Figure 1 As shown, it includes a first electrode layer 110 and a hole transport layer 120 , a perovskite light absorption layer 130 , an electron transport layer 140 and a second electrode layer 150 which are sequentially stacked on the first electrode layer 110 .

[0224] A method for preparing a perovskite solar cell comprises the following steps:

[0225] 1) Preparation of the first electrode layer: Using FTO conductive glass as the first electrode, ultrasonically clean the FTO conductive glass with a size of 2.0 cm×2.0 cm in detergent, deionized water, and anhydrous ethanol for 30 minutes, and then dry it for later use; treat the FTO glass with ultraviolet ozone for 15 minutes, and ultrasonically clean the etched FTO conductive glass with water and anhydrous ethanol for several times.

[0226] 2) Preparing a hole transport layer on the first electrode layer: Weigh 5 mg of the hole transport material A1 prepared in Example A1 and dissolve it in 1 mL of chlorobenzene to obtain a hole transport layer solution, and spin-coat the hole transport layer solution on the FTO conductive glass at 5000 rpm / s. After the spin coating is completed, anneal at 100° C. for 5 min to obtain a hole transport layer (thickness of ).

[0227] 4) Preparation of a perovskite light-absorbing layer on the hole transport layer: Weigh 223 mg of lead iodide (PbI2), 80 mg of iodomethane (FAI), and 15 mg of methyl chloride (MACl) and dissolve them in a mixed solution of 0.8 mL of DMF and 0.2 mL of DMSO, stir for 3 h, filter with a 0.22 μm organic filter membrane to obtain a perovskite precursor solution, spin coat the perovskite precursor solution on the hole transport layer at 3000 rpm / s, anneal at 100°C for 20 min, and cool to room temperature to form a perovskite light-absorbing layer with a thickness of 700 nm.

[0228] 5) Prepare an electron transport layer on the perovskite light absorption layer: Put the obtained wafer into the evaporation machine and evaporate the electron transport layer C60 and a hole blocking layer BCP with a thickness of 27 nm and 8 nm, forming an electron transport layer.

[0229] 6) Preparing a second electrode layer on the electron transport layer: placing the obtained wafer into a vapor deposition machine, vapor-depositing a metal electrode Ag with a thickness of 100 nm, and obtaining a perovskite solar cell, which is recorded as a cell device S-1.

[0230] Example B2

[0231] The same as Example B1, except that in step 3), the material A1 is replaced by the hole transport material A2 prepared in Example 2 for preparing the hole transport layer. The obtained perovskite solar cell is recorded as cell device S-2.

[0232] Example B3

[0233] The same as Example B1, except that in step 3), the material A1 is replaced by the hole transport material A3 prepared in Example 3 for preparing the hole transport layer. The obtained perovskite solar cell is recorded as cell device S-3.

[0234] Example B4

[0235] The same as Example B1, except that in step 3), the material A1 is replaced by the hole transport material A4 prepared in Example 4 for preparing the hole transport layer. The obtained perovskite solar cell is recorded as cell device S-4.

[0236] Example B5

[0237] The same as Example B1, except that in step 3), material A1 is replaced by a mixture of material A1 (hole transport material prepared in Example 1) and material A2 (hole transport material prepared in Example 2) in a mass ratio of 3:1 to prepare a hole transport layer. The obtained perovskite solar cell is recorded as cell device S-5.

[0238] Comparative Example 1

[0239] Same as Example B1, except that: in step 3), material A1 is replaced with PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) to prepare the hole transport layer. The obtained perovskite solar cell is recorded as cell device DS-1.

[0240] Performance Test:

[0241] (1) Test of material hole mobility:

[0242] The hole mobility of the tested material is determined by the space charge limited current (SCLC) method, which is the hole mobility of the hole transport layer.

[0243] The structure of the test device is FTO|Example|PVK|Spiro-OMeTAD|Cu. Taking the test device of the hole transport material A1 provided in Example A1 as an example, the preparation process of the test device is as follows:

[0244] 1) Preparation of the first electrode layer: FTO conductive glass with a specification of 2.0 cm×2.0 cm is used as the first electrode, and then the FTO conductive glass is ultrasonically cleaned in detergent, deionized water and anhydrous ethanol for 30 minutes in sequence, and then dried for use; the FTO glass is then treated with ultraviolet ozone for 15 minutes, and the etched FTO conductive glass is ultrasonically cleaned with water and anhydrous ethanol in sequence for several times.

[0245] 2) Preparing a hole transport layer on the first electrode layer: Weigh 5 mg of the hole transport material A1 prepared in Example A1 and dissolve it in 1 mL of chlorobenzene to obtain a hole transport layer solution, and spin-coat the hole transport layer solution on the FTO conductive glass at 5000 rpm / s. After the spin coating is completed, anneal at 100° C. for 5 min to obtain a hole transport layer (thickness of ).

[0246] 4) Prepare a perovskite light-absorbing layer on the hole transport layer: weigh 223 mg of lead iodide (PbI2), 80 mg of iodomethane (FAI), and 15 mg of methyl chloride (MACl), dissolve them in a mixed solution of 0.8 mL of DMF and 0.2 mL of DMSO, stir for 3 h, filter with a 0.22 μm organic filter membrane to obtain a perovskite precursor solution, spin coat the perovskite precursor solution on the hole transport layer at 3000 rpm / s, anneal at 100°C for 20 min, and cool to room temperature to form a perovskite light-absorbing layer with a thickness of 500 nm.

[0247] 5) Prepare a hole transport layer on the perovskite light absorbing layer: Dissolve Spiro-OMeTAD in chlorobenzene at a concentration of 72.3 mg / mL, add 28.8 μL of 4-tert-butylpyridine and 28.8 μL of 520 mg / mL Li-TFSI in acetonitrile. Filter with a filter membrane, take 70 μL on the perovskite light absorbing layer, rotate the Spiro at 3000 rpm, and form a hole transport layer after spin coating.

[0248] The method for preparing the test device of the hole transport material A2 prepared in Example 2 is the same as the preparation process of the above-mentioned test device, except that the hole transport material A1 prepared in Example A1 in step 2) is replaced by the hole transport material A2 prepared in Example 2.

[0249] The method for preparing the test device of the hole transport material A3 prepared in Example 3 is the same as the preparation process of the above-mentioned test device, except that the hole transport material A1 prepared in Example A1 in step 2) is replaced by the hole transport material A3 prepared in Example 3.

[0250] The method for preparing the test device of the hole transport material A4 prepared in Example 4 is the same as the preparation process of the above-mentioned test device, except that the hole transport material A1 prepared in Example A1 in step 2) is replaced by the hole transport material A4 prepared in Example 4.

[0251] The method for preparing a test device in which material A1 and material A2 are compounded as hole transport materials is the same as the preparation process of the above-mentioned test device, except that the hole transport material A1 prepared in Example A1 in step 2) is replaced by a mixture of material A1 (hole transport material prepared in Example 1) and material A2 (hole transport material prepared in Example 2) in a mass ratio of 3:1.

[0252] The preparation method of the test device of the hole transport material D1 provided in Comparative Example 1 is the same as the preparation process of the above test device, except that the hole transport material A1 prepared in Example A1 in step 2) is replaced by PTAA.

[0253] The test results are shown in Table 1. As can be seen from Table 1, the materials A1 to A4 provided in the embodiments of the present application have significantly higher hole mobility, especially, the compounding of materials A1 and A2 as hole transport materials can reduce the energy barrier between the perovskite light absorption layer and the lower interface, effectively reduce the loss of hole transport, and have higher hole mobility.

[0254] Table 1

[0255] <![CDATA[Hole mobility (cm 2 ·V -1 ·s -1 )]]> Material A1 <![CDATA[1.73×10 -4 ]]> Material A2 <![CDATA[3.58×10 -3 ]]> Material A3 <![CDATA[4.82×10 -4 ]]> Material A4 <![CDATA[6.53×10 -4 ]]> Material A1+A2 <![CDATA[1.91×10 -3 ]]> PTAA <![CDATA[1.53×10 -4 ]]>

[0256] (2) Wettability test

[0257] The structure of the test device is FTO|embodiment. The preparation process of the test device is as follows:

[0258] 1) Preparation of the first electrode layer: FTO conductive glass with a specification of 2.0 cm×2.0 cm is used as the first electrode, and then the FTO conductive glass is ultrasonically cleaned in detergent, deionized water and anhydrous ethanol for 30 minutes in sequence, and then dried for use; the FTO glass is then treated with ultraviolet ozone for 15 minutes, and the etched FTO conductive glass is ultrasonically cleaned with water and anhydrous ethanol in sequence for several times.

[0259] 2) Preparing a hole transport layer on the first electrode layer: Weigh 5 mg of hole transport material (the hole transport materials prepared in Examples 1 to 4 and Comparative Example 1 are provided respectively) and dissolve in 1 mL of chlorobenzene to obtain a hole transport layer solution, spin coat the hole transport layer solution on the FTO conductive glass at 5000 rpm / s, and anneal at 100° C. for 5 min after spin coating to obtain a hole transport layer (thickness is ).

[0260] The test method is:

[0261] 1) Focus. Fix the injector or micro-syringe on the stage, adjust the camera focus, and then rotate the knob behind the camera base to adjust the distance from the camera to the stage to make the image clearest.

[0262] 2) Add the sample. Use the micro syringe to push out 0.6μL to 1.0μL of liquid. At this time, a clear small droplet can be seen at the bottom of the injector in the live image.

[0263] 3) Sample collection. Rotate the knob on the stage base to make the stage rise slowly, touch the droplet hanging at the bottom of the injector, and then descend, leaving the droplet on the solid surface.

[0264] 4) Freeze the image. After receiving the sample, click the freeze image button in the upper right corner of the interface within 20 seconds to freeze the screen. Then click Save as in the File menu to save the image in a folder.

[0265] 5) Measure the angle. Click the angle measurement method button to enter the main interface of the angle measurement method, press the start key, and open the previously saved image. At this time, a measuring ruler composed of two straight lines crossing at 45° appears on the image. Use the Z, X, Q, A keys on the keyboard, i.e. the left, right, up, and down keys, to adjust the position of the measuring ruler: first, make the measuring ruler tangent to the edge of the droplet, then move the measuring ruler down so that the intersection is at the top of the droplet, and then use the < and > keys on the keyboard, i.e. the left and right keys, to rotate the measuring ruler so that it intersects with the left end of the droplet, and then get the value of the contact angle.

[0266] The test results are shown in Table 2 below. It can be seen from Table 2 that the hole transport material provided in the embodiment of the present application has a lower contact angle with water and the perovskite raw material (diiodomethane). This can intuitively show that the hole transport material provided in the embodiment of the present application has a higher wettability and is more conducive to forming a continuous and uniform perovskite layer on its surface.

[0267] Table 2 Wettability test results

[0268]

[0269] (3) Battery performance test

[0270] Using Keithley2400SMU, AM1.5Gsolarirradiation at 1000W / m 2The prepared perovskite solar cell was tested under a light source, and the energy conversion efficiency Eff was calculated according to the following formula: Eff = Pout / Popt = Voc×Jsc×(Vmpp×Jmpp) / (Voc×Jsc) = Voc×Jsc×FF, where Pout, Popt, Vmpp, and Jmpp are the battery operating output power, incident light power, battery maximum power point voltage, and maximum power point current, respectively, and Voc, Jsc, and FF are open circuit voltage, short circuit current density, and fill factor, respectively. See Table 2 for specific results. It can be seen from Table 2 that when the hole transport material provided in the embodiment of the present application is used to prepare a solar cell, the battery device has a higher battery conversion efficiency.

[0271] Table 2

[0272]

[0273] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A hole transport material, characterized in that: The molecular structure of the hole transport material is shown in Formula I: Wherein, R1 includes an acidic group; n is a natural number between 1 and 5; when n is 1, R2 is the same as R1, and when n=2 to 5, R2 is hydrogen or the same as R1.

2. The hole transport material according to claim 1, characterized in that R1 includes any one of A-COOH, A-SO3H, A-PO3H2, and A-BO2H2; wherein A includes C0~C 10 Alkyl, C0~C 10 Any one of the alkoxy groups.

3. The hole transport material according to claim 2, characterized in that The C0~C 10 The alkyl group includes any one of a C1-C4 straight chain alkyl group and a C5-C8 cycloalkyl group. 10 The alkoxy group includes any one of C1 to C4 straight chain alkoxy groups.

4. The hole transport material according to any one of claims 1 to 3, characterized in that The hole transport material includes at least one of the compounds shown in Formula Ia-Formula Id:

5. The hole transport material according to claim 4, characterized in that The hole transport material includes a compound represented by Formula Ia and a compound represented by Formula Ib, and the mass ratio of the compound represented by Formula Ia to the compound represented by Formula Ib is (2-3):(0.5-1.5).

6. A method for preparing a hole transport material, characterized in that: The following steps are involved: Using the compound represented by formula II and the compound represented by formula III as monomers, a polymerization reaction is carried out to obtain the hole transport material represented by any one of claims 1 to 5; or, Using the compound represented by formula IV and the compound represented by formula V as monomers, an Ullmann coupling reaction is carried out to obtain the hole transport material represented by any one of claims 1 to 5; Wherein, X includes any one of the halogen elements.

7. The method for preparing a hole transport material according to claim 6, characterized in that: The X includes any one of bromine, chlorine and iodine.

8. The method for preparing a hole transport material according to claim 6 or 7, characterized in that: The polymerization reaction step comprises: subjecting the compound represented by formula II to a substitution reaction, so that the X atom in the compound represented by formula II is replaced by a borate group, and then subjecting the compound represented by formula II or the compound represented by formula III to a Suzuki coupling reaction; or, The polymerization reaction step comprises: subjecting the compound represented by formula III to a substitution reaction so that the X atom in the compound represented by formula III is replaced by a borate group, and then subjecting the compound represented by formula II or the compound represented by formula III to a Suzuki coupling reaction.

9. The method for preparing a hole transport material according to claim 8, characterized in that: The Suzuki coupling reaction is carried out under the condition of a first catalyst, wherein the first catalyst comprises tetrakis(triphenylphosphine)palladium and potassium carbonate; and / or The reaction temperature of the Suzuki coupling reaction is 70-90°C.

10. The method for preparing a hole transport material according to any one of claims 6 to 9, characterized in that: The Ullmann coupling reaction is carried out under the condition of a second catalyst, wherein the second catalyst includes cuprous iodide, sodium tert-butoxide and 1-10,1-phenanthroline.

11. A solar cell comprising a hole transport layer, characterized in that: The hole transport layer comprises the hole transport material according to any one of claims 1 to 5 and / or the hole transport material prepared by the method for preparing the hole transport material according to any one of claims 6 to 10.

12. The solar cell according to claim 11, wherein: The solar cell includes a first electrode layer, a perovskite light absorption layer, a hole transport layer and a second electrode layer.

13. The solar cell according to claim 11 or 12, characterized in that: The thickness of the hole transport layer is And / or, the hole mobility of the hole transport layer is 1.73×10 -4 ~3.58×10 -3 cm 2 ·V -1 ·s -1 .

14. The solar cell according to claim 11 or 12, characterized in that: The band gap of the perovskite light absorbing layer is 1.10 to 2.0 eV; and / or the thickness of the perovskite light absorbing layer is between 600 and 800 nm.

15. A photovoltaic module, characterized in that: The invention comprises a solar cell as claimed in any one of claims 11 to 14.

16. A photovoltaic device, characterized in that: Comprising the photovoltaic module as claimed in claim 15.

Citation Information

Cited By

  • Organic compound, solar cell and use thereof

    WO2025200913A1

  • Organic compound, solar cell, photovoltaic module, photovoltaic system, electric device and power-generating device

    WO2025200959A1